Utilization of Health Facilities by Pregnant Women at Pekauman Community Health Center, Banjarmasin, Indonesia - Vonny Khresna Dewi; Rita Kirana; Muhammad Mukhtar (Tropical Health and Medical Research, 2021)
The purpose of this study is to analyze the relationship between the use of government health facilities with predisposing factors (preference and self-efficacy) and reinforcing factors (support) in pregnant women. This survey research with a cross-sectional study design was conducted in the Pekauman Community Health Center's working area in Banjarmasin, Indonesia, with 125 respondents who had babies aged ? six months who lived in the Pekauman Community Health Center's working area who visited the integrated service post in August 2017. The analysis was performed using the Chi-Square test. The results of the study 89 respondents (71.2%) made use of antenatal care facilities; 92 respondents (73.6%) chose health facilities; 88 respondents (70, 4%) have high self-efficacy; 78 respondents (62.4%) received support (family, friends, social groups). This research concludes that there is a relationship between the preferences of pregnant women (p= 0.025) with the use of antenatal services in government health facilities; There was no relationship between self-efficacy (p= 0.096); there is no relationship between family support, friends, social groups (p= 0.227) with the use of antenatal care for pregnant women in government health facilities. It is suggested to conduct further research on the relationship between antenatal services for pregnant women in government health facilities with the completeness of health facilities and the level of respondent satisfaction.